Stress Management as an Effective Complementary Therapeutic Strategy for Weight Loss in Children and Adolescents with Obesity: A Systematic Review of Randomized Controlled Trials - George Paltoglou; George P. Chrousos; Flora Bacopoulou (MDPI AG, 2021)
Lifestyle intervention programs, including mindfulness and stress management/emotional control training techniques have been infrequently studied in children. The aim of this systematic review was to assess whether implementing stress management/emotional control training strategies in the context of a body weight loss program in children and adolescents is associated with improved body weight outcome in this age group. A systematic literature search was conducted to identify relevant studies published before 31 December 2020 in the following databases: Medline (PubMed), Scopus, and Cochrane Central Registry of Controlled Trials. Only randomized clinical trials (RCTs) on mindfulness or stress management in children and adolescents with obesity were included in this systematic review. Six RCTs fulfilled the study inclusion criteria and included intervention (112 subjects) and control (137 subjects) groups. The interventions used were Mindfulness-Based Stress Reduction therapy for 8 weeks (three studies), a mindfulness-based group program for adolescents (one study), and Mindful Eating Intervention for 6 weeks (one study) and 10 weeks (one study). The intervention group demonstrated reduced adiposity markers as compared to controls in four of the six included studies. The presented studies support the hypothesis that a structured, mindfulness-based intervention program may lead to a decrease in the biomarkers of obesity.